Cover Image, Volume 16, Issue 2. (8th May 2018) - Dressel, S.; Gosselin, M.‐C.; Capstick, M. H.; Carrasco, E.; Weyland, M. S.; Scheidegger, S.; Neufeld, E.; Kuster, N.; Bodis, S.; Rohrer Bley, C.
Abstract : The cover image, by S. Dressel et al., is based on the Original Article Novel hyperthermia applicator system allows adaptive treatment planning: Preliminary clinical results in tumour‐bearing animals, DOI:10.1111/vco.12340 Abstract : The cover image, by S. Dressel et al., is based on the Original Article Novel hyperthermia applicator system allows adaptive treatment planning: Preliminary clinical results in tumour‐bearing animals, DOI:10.1111/vco.12340